Method for improving performance of solar cell based on self-cleaning structure of coupling of siO2 microporous film and znO nanorod
Patent Information
- Application Number
- CN202510555586.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2026-10-27
AI Technical Summary
Elminir等人通过对自清洁原理的详细研究以及太阳能表面粉尘对其系统性能的影响的估计,发现无法进行自清洁的光伏发电系统其输出功率每月下降约17.4%
[0023](1)本发明创新性地构建了SiO2@ZnO网状微孔薄膜的分级自清洁结构,SiO2薄膜上独特的微米孔洞结构,可以增加薄膜的透光率,从而在微纳复合结构确保超疏水性的同时,提高电池的光电转换效率;
Smart Images

Figure CN122995341A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solar cells, specifically relating to a new method for improving the performance of solar cells by using a self-cleaning structure of SiO2 microporous thin film coupled with ZnO nanorods. Background Technology
[0002] In recent years, with the overexploitation of non-renewable energy sources and the deepening of environmental pollution, countries around the world have begun to continuously adjust and update their energy industry structures. To address the critical issues of energy depletion and environmental pollution—issues concerning human survival—a pressing problem is how to obtain inexpensive and environmentally friendly clean energy. Developing solar energy is an effective means to achieve this goal. This is mainly because the solar radiation energy received by the Earth's surface is 1.2 × 10⁻⁶ kilowatts. 17 W, while the world's total energy production capacity is currently only 1.4 × 10⁻⁶. 13 W. Solar cells are widely considered one of the most effective means of utilizing solar energy.
[0003] Because photovoltaic (PV) modules require a large footprint and have stringent requirements for sunlight, an increasing number of solar power plants are being installed in sparsely populated but harsh, dusty areas, such as desolate Gobi and desert regions. These areas possess abundant solar energy resources, and since the land there is difficult to use for other purposes, the installation of solar power plants undoubtedly greatly improves land utilization. However, the natural environment in which PV modules are located is rich in dust and other solid microparticles, which are easily adsorbed onto the surface of the solar panels, severely impacting the conversion efficiency and lifespan of the PV power generation system. Research shows that dust accumulation is the most important factor affecting the energy conversion efficiency of PV modules. Simultaneously, rainwater adhering to the cell surface refracts and reflects light, significantly reducing photoelectric conversion efficiency. Relying on traditional post-cleaning methods (manual large-area rinsing, washing, and wiping) to clean PV devices not only consumes a large amount of manpower, material resources, and financial resources but may also damage the PV modules. Long-term contaminant adhesion is not only difficult to clean but may also cause hot spot effects, damaging the PV modules and thus reducing their lifespan. Our preliminary research revealed that currently, the vast majority of photovoltaic (PV) cell devices in China are cleaned manually, with the frequency varying significantly depending on the level of contamination in different regions. In Qufu, Shandong, this frequency is even as high as once a week. Therefore, introducing a superhydrophobic self-cleaning film onto the surface of solar panels presents a potentially effective cleaning method.
[0004] Since German botanists Barthlott and Neinhuis first reported the relationship between the microstructure of lotus leaf surfaces and their self-cleaning function in 1997, more and more researchers have focused on biomimetic superhydrophobic self-cleaning functional layers. Generally, when a superhydrophobic surface comes into contact with water droplets or dust, there is only a very small contact area, making it easy for surface contaminants to be removed by external forces such as airflow or water droplets, thus achieving a self-cleaning effect, known as the "lotus leaf self-cleaning effect." Structurally, the lotus leaf surface has micron-sized papillae with nano-sized wax crystals. This micro-nano-scale rough structure significantly increases the contact angle of water droplets, causing them to roll off easily. The movement of water droplets on a superhydrophobic surface is a complex physical phenomenon that plays a crucial role in the self-cleaning process: as water droplets roll on the surface, they carry away surface contaminants or dust, achieving a self-cleaning effect. Applying this to device surfaces can greatly reduce the energy consumption required for surface cleaning.
[0005] In 2024, Zhang Hui et al., referencing the surface of natural lotus leaves, used polydimethylsiloxane (PDMS) elastomer as a soft template and combined it with ultraviolet curing technology to prepare a superhydrophobic surface with a microemulsion structure, achieving a static water contact angle of 150°. In 2015, Fang, Y et al. studied the microstructure and wettability of butterfly wing surfaces, establishing a micro / nanostructure model of the hydrophobicity of butterfly wing surfaces based on the Cassie equation. In 2020, Zhang Dehu et al. used the sol-gel method to prepare a silicon film on a substrate material by controlling the mixing ratio of tetraethoxysilane and polypropylene glycol, and then modified it to obtain a superhydrophobic silicon film with a static water contact angle of 159°. In 2019, Liu Pengfei et al. used a hydrothermal method to prepare a dandelion-shaped zinc oxide film on a graphite surface using formamide and zinc flakes, achieving a static water contact angle of 155°. In 2014, Fei Ting et al. prepared a superhydrophobic transparent coating using a template deposition method after modification with hexadecyltrimethoxysilane (CTMS). Its static water contact angle reached 166.1°. In 2022, Saini et al. conducted an in-depth study on the self-cleaning properties of TiO2 thin films using nano-TiO2, finding that the self-cleaning ability of the film was very significant, increasing power generation by approximately 4%. Elminir et al., through detailed research on the self-cleaning principle and estimation of the impact of dust on solar cell surface performance, found that photovoltaic power generation systems that cannot self-clean experience a monthly power output decrease of approximately 17.4%.
[0006] Current research on photovoltaic devices mainly focuses on device improvement and the development of new devices, while the impact of dust pollution on photovoltaic devices has not received sufficient attention and is rarely reported in the literature. Therefore, this invention focuses on reducing the impact of dust pollution on photovoltaic devices.
[0007] This invention uses solar cells as the main body and constructs a hierarchical cleaning structure to achieve the self-cleaning function of photovoltaic modules, thereby reducing the impact of dust pollution on photoelectric conversion efficiency. The invention constructs a hierarchical self-cleaning structure on the light-facing side of the solar cell, consisting of a highly transparent SiO2 microporous membrane coupled with ZnO nanorods. First, appropriate raw materials and solvents are selected, and a layer of polystyrene@silica mixed suspension is spin-coated onto an FTO glass substrate. Then, high-temperature calcination causes the polystyrene microspheres to disappear, leaving micron-sized pores on the SiO2 film. Next, ZnO seed solution is spin-coated onto the SiO2 microporous membrane, and ZnO nanorods are grown using a hydrothermal deposition method to construct a micro / nano hierarchical composite structure, thus achieving the self-cleaning function of the photovoltaic device and preventing dust pollution from affecting its performance. This biomimetic micro / nano structure also holds promise for applications in dust-proof self-cleaning in fields such as glass curtain walls and automotive windshields. Summary of the Invention
[0008] To address the vulnerability of photovoltaic device surfaces to solid particulate contaminants such as dust and particulate matter, this invention proposes a method for improving solar cell performance using a hierarchical self-cleaning structure of a highly transparent SiO2 microporous film coupled with ZnO nanorods. Compared to existing self-cleaning structures, this thin-film structure significantly improves light transmittance while maintaining the superhydrophobicity of the micro / nano hierarchical composite structure.
[0009] The primary objective of this invention is to obtain a method for preparing a self-cleaning film of SiO2 microporous film coupled with ZnO nanorods;
[0010] The second objective of this invention is to obtain a photovoltaic device with a self-cleaning structure based on SiO2 microporous thin film coupled with ZnO nanorods, making it highly suitable for use in solar cells.
[0011] In a first aspect, the present invention provides a method for preparing a self-cleaning film of SiO2 microporous film coupled with ZnO nanorods for improving the performance of solar cells, the steps of which include:
[0012] (1) The FTO conductive glass was ultrasonically cleaned for 40 minutes each with deionized water, acetone, isopropanol and anhydrous ethanol, dried with nitrogen, and then cleaned in the oxygen plasma cleaner for 15 minutes to obtain clean and dry FTO.
[0013] (2) A silica microsphere suspension with an average sphere diameter of 10 nm was prepared by sol-gel method. A certain volume of polystyrene microsphere suspension with an average sphere diameter of 800 nm was added to the suspension in proportion to obtain a polystyrene@silica mixed suspension.
[0014] (3) Place the FTO glass substrate on a spin coater at a speed of 60-70 r / min and uniformly drop 105 μL of polystyrene@silica mixed suspension. After spin coating, remove the polystyrene microspheres at a high temperature of about 30 min on a hot plate at 350℃. Spin coat the SiO2 microporous film with ZnO seed solution, and then place it in a 90℃ constant temperature water bath for a certain period of time. After the ZnO nanorods have grown, anneal the FTO glass substrate at 500℃ for 1 h.
[0015] (4) Prepare a set of glass petri dishes of appropriate size and clean them thoroughly. Place one glass petri dish at the bottom of the vacuum desiccator and add 50 μL of heptadecafluorodecyltrimethoxysilane to the petri dish. Place the other glass petri dish on the perforated ceramic partition in the middle of the vacuum desiccator and place the sample to be modified into the petri dish. Simply treat the seal of the vacuum desiccator with Vaseline, close the vacuum desiccator, and ensure that it is completely sealed. Connect the vacuum desiccator and the vacuum pump, adjust the glass stopcock on the vacuum desiccator, turn on the vacuum pump, evacuate for about 10 minutes, and then close the stopcock on the vacuum desiccator. Gently lift the entire vacuum desiccator and place it in the drying oven, allowing it to react at 95°C for a certain period of time. After the drying oven stops working and cools to room temperature, the modification is complete.
[0016] A second aspect of the present invention provides a photovoltaic device with improved self-cleaning structure based on SiO2 microporous thin film coupled with ZnO nanorods, the steps of which include:
[0017] (1) The FTO glass substrate was ultrasonically treated in deionized water, acetone, isopropanol and ethanol for 40 minutes. After drying with nitrogen, the FTO glass substrate was treated with ultraviolet ozone for 15 minutes to obtain clean and dry FTO;
[0018] (2) Based on the specific type of photovoltaic device (such as perovskite, sulfide, selenide, etc.), select an appropriate deposition method (such as spin coating, thermal evaporation, hydrothermal deposition, etc.) to deposit the photovoltaic absorption layer material on the self-cleaning structure of SiO2 microporous thin film coupled with ZnO nanorods;
[0019] (3) A hole transport layer and an electron transport layer are deposited sequentially above the photovoltaic absorption layer. The specific materials and deposition methods are determined according to the device design.
[0020] (4) The back electrode (such as gold, silver, aluminum, etc.) is prepared by thermal evaporation or magnetron sputtering, with a thickness of about 10 nm.
[0021] (5) Devices that have been packaged and prepared according to standard processes.
[0022] Compared with the prior art, the present invention has the following advantages and positive effects:
[0023] (1) This invention innovatively constructs a hierarchical self-cleaning structure of SiO2@ZnO mesh microporous film. The unique micron-sized pore structure on the SiO2 film can increase the light transmittance of the film, thereby improving the photoelectric conversion efficiency of the battery while ensuring superhydrophobicity in the micro-nano composite structure.
[0024] (2) In this invention, the SiO2 micron-sized hole structure acts like a concave lens, which can redistribute and focus sunlight in free space, thereby significantly improving the light intensity of the incident light and indirectly enhancing the light transmission performance of the structure, thereby improving the photoelectric conversion efficiency of the battery.
[0025] (3) This invention provides new ideas and methods for the research and development of superhydrophobic thin films for solar cells and their photovoltaic applications;
[0026] (4) The ZnO nanorod material selected in this invention has a large “absorption rate” in the ultraviolet light band, which can greatly reduce the damage of ultraviolet light to photovoltaic devices. Moreover, after absorbing ultraviolet light, ZnO will emit visible light, thereby increasing the “transmittance” of light.
[0027] (5) The method of the present invention is simple, relatively inexpensive and easy to implement. Attached Figure Description
[0028] To make the objectives, technical solutions, and advantages of this invention clearer, the following describes the invention in further detail using antimony selenide sulfide solar cells as an example and in conjunction with specific embodiments, with reference to the accompanying drawings, wherein:
[0029] Figure 1 This is a schematic diagram of the structure of antimony selenide sulfide solar cells, which improves the self-cleaning structure of SiO2 microporous thin films coupled with ZnO nanorods. Detailed Implementation
[0030] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed under conventional conditions. Unless otherwise defined or stated, the technical and scientific terms used herein have the same meaning as those familiar with the art. Furthermore, any methods and materials similar to or equivalent to those described herein can be applied to the methods of the present invention.
[0031] Example 1: Preparation of a self-cleaning film of SiO2 microporous film coupled with ZnO nanorods using the present invention.
[0032] (1) The FTO conductive glass was ultrasonically cleaned for 40 minutes each with deionized water, acetone, isopropanol and anhydrous ethanol, dried with nitrogen, and then cleaned in the oxygen plasma cleaner for 15 minutes to obtain clean and dry FTO.
[0033] (2) A silica microsphere suspension with an average sphere diameter of 10 nm was prepared by sol-gel method. A certain volume of polystyrene microsphere suspension with an average sphere diameter of 800 nm was added to the suspension in proportion to obtain a polystyrene@silica mixed suspension.
[0034] (3) Place the FTO glass substrate on a spin coater. The spin coater speed is 6070 r / min. Uniformly drop 105 μL of polystyrene@silica mixed suspension. After spin coating, remove the polystyrene microspheres at a high temperature of about 30 min on a 350℃ hot stage.
[0035] (4) Spin-coat ZnO seed solution onto SiO2 microporous film, and then place it in a 90℃ constant temperature water bath for a certain period of time.
[0036] (5) After the ZnO nanorods were grown, the FTO glass substrate was annealed at 500℃ for 1 hour.
[0037] (6) Prepare a set of glass petri dishes of appropriate size and clean them. Place one glass petri dish at the bottom of the vacuum desiccator and add 50 μL of heptadecafluorodecyltrimethoxysilane to the petri dish.
[0038] (7) Place another glass petri dish on the perforated ceramic partition in the middle of the vacuum desiccator, and place the sample to be modified into the petri dish;
[0039] (8) Simply treat the seal of the vacuum dryer with petroleum jelly, cover the vacuum dryer, and ensure that it is completely sealed;
[0040] (9) Connect the vacuum dryer and the vacuum pump, adjust the glass piston on the vacuum dryer, turn on the vacuum pump, evacuate for about 10 minutes, and then turn off the piston on the vacuum dryer.
[0041] (10) Gently lift the entire vacuum dryer and place it in the drying oven, allowing it to react at 95°C for a certain period of time. Once the drying oven stops working and cools to room temperature, the modification is complete.
[0042] Example 2 : Antimony selenide solar cells based on this self-cleaning thin film structure were fabricated using this invention.
[0043] (1) The FTO conductive glass was ultrasonically cleaned for 40 minutes each with deionized water, acetone, isopropanol and anhydrous ethanol, dried with nitrogen, and then cleaned in the oxygen plasma cleaner for 15 minutes to obtain clean and dry FTO.
[0044] (2) A self-cleaning film of SiO2 microporous film coupled with ZnO nanorods was prepared according to Example 1;
[0045] (3) Weigh out appropriate amounts of thiourea and selenourea and dissolve them in an appropriate amount of deionized water, stirring until homogeneous. Add an appropriate amount of antimony chloride and continue stirring until completely dissolved to obtain a homogeneous precursor solution;
[0046] (4) Place the FTO substrate prepared in step (2) into a spin coater and spin coat the precursor solution prepared in step (3). After spin coating, place the substrate in an oven and dry it at 100°C for 10 minutes to remove the solvent;
[0047] (5) Place the spin-coated precursor film into a tube furnace and heat it to 300°C under a nitrogen atmosphere. Hold the temperature for 30 minutes to carry out the selenization reaction and form an Sb2(S,Se)3 film. After cooling to room temperature, remove the film, rinse it with deionized water and anhydrous ethanol, and dry it with nitrogen.
[0048] (6) Spin-coat a hole transport material onto the surface of the Sb2(S,Se)3 thin film, and then anneal at 120°C for 10 minutes;
[0049] (7) A metal back electrode (such as gold or silver) with a thickness of about 10 nm is prepared above the hole transport layer by means of thermal evaporation or magnetron sputtering.
[0050] (8) The prepared solar cells are packaged according to standard processes to ensure the stability and performance of the device.
[0051] Example 3: Fabrication of antimony sulfide solar cells based on this self-cleaning thin film structure using the present invention.
[0052] (1) The FTO conductive glass was ultrasonically cleaned for 40 minutes each with deionized water, acetone, isopropanol and anhydrous ethanol, dried with nitrogen, and then cleaned in the oxygen plasma cleaner for 15 minutes to obtain clean and dry FTO.
[0053] (2) A self-cleaning film of SiO2 microporous film coupled with ZnO nanorods was prepared according to Example 1;
[0054] (3) Measure out cadmium nitrate solution and ammonia solution, pour them into a beaker in sequence, and stir for 150s. Then add thiourea solution, stir for 30s, add 70ml of ultrapure water, and continue stirring for 30s to prepare the precursor solution;
[0055] (4) Place the FTO substrate obtained in step (2) into a beaker and pour in the precursor solution prepared in step (3);
[0056] (5) Place the sealed beaker from step (4) into a constant temperature water bath. Set the water bath temperature to 70°C, the heating time to 10 min, and react at 70°C for 16 min. Then remove the beaker and allow it to cool naturally to room temperature.
[0057] (6) The film obtained by deposition in step (5) is rinsed with ultrapure water and anhydrous ethanol in sequence, dried with nitrogen, and heated on a 100°C hot plate for 10 min to remove the solvent. After cooling, a methanol solution containing cadmium chloride is spin-coated onto the cadmium sulfide surface, and then annealed in air on a 400°C hot plate for 10 min.
[0058] (7) Weigh out potassium antimony tartrate hemihydrate and sodium thiosulfate pentahydrate and dissolve them in 40 ml of ultrapure water. Stir thoroughly to ensure complete dissolution. After stirring the mixed solution thoroughly, the precursor solution is ready.
[0059] (8) Put the FTO obtained in step (6) into the inner liner of the autoclave and pour in the precursor solution prepared in step (3);
[0060] (9) Place the sealed hydrothermal reactor from step (4) into an oven. Set the oven temperature to 120°C, the heating time to 13 min, and react at 120°C for 3 h. Then remove the hydrothermal reactor and allow it to cool naturally to room temperature.
[0061] (10) After the hydrothermal process is completed, the deposited precursor membrane is removed, rinsed with ultrapure water and anhydrous ethanol in sequence, and dried with nitrogen. Under a nitrogen atmosphere, the precursor membrane is placed on a heating plate and heat-treated at 100°C for 2 min;
[0062] (11) Spin-coat a hole transport material onto the surface of the Sb2S3 thin film, and then anneal at 120°C for 10 minutes;
[0063] (12) After cooling, a back electrode (gold or silver, etc.) is prepared on top of the hole transport layer using a vacuum deposition method;
[0064] (13) After cooling, continue annealing at 350°C for 10 minutes on a heating plate;
[0065] (14) Package solar cells according to standard processes.
Claims
1. A method for improving solar cell performance based on a self-cleaning structure of SiO2 microporous thin film coupled with ZnO nanorods. The key lies in ensuring that the micro-nano hierarchical composite structure has superhydrophobicity while having greater "transmittance" to sunlight, that is, the structure has excellent anti-reflection properties to optimize cell performance. The structure is summarized as follows: FTO substrate: A transparent conductive oxide (Fluorine-doped Tin Oxide, FTO) substrate is used to ensure good light transmittance and conductivity; SiO2 microporous film: A polystyrene@silica mixed suspension is spin-coated onto an FTO glass substrate, and then the polystyrene microspheres are destroyed by high-temperature calcination, leaving micron-sized pores on the SiO2 film; SiO2 microporous film coupled with ZnO nanorods: ZnO seed solution is spin-coated on SiO2 microporous film, and ZnO nanorods are grown by hydrothermal deposition to construct a micro-nano hierarchical composite structure, thereby realizing the self-cleaning function of photovoltaic devices and avoiding dust pollution from affecting the performance of photovoltaic devices. Cadmium sulfide electron transport layer: The CdS layer, as an electron transport layer, has a wide band gap, which can effectively transport photogenerated electrons from the absorption layer to the FTO substrate; Metal back electrode: Gold is selected as the back electrode.
2. An innovative method for fabricating solar cells, based on the optimization of a self-cleaning structure of SiO2 microporous thin film coupled with ZnO nanorods, particularly the fabrication of a self-cleaning film of SiO2 microporous thin film coupled with ZnO nanorods on an FTO glass substrate, which maintains the superhydrophobicity of the micro / nano hierarchical composite structure while exhibiting excellent anti-reflection properties, specifically including the following steps: (1) FTO substrate pretreatment: First, the conductive surface of the FTO substrate is thoroughly cleaned to remove surface impurities and ensure the high quality of the subsequent deposited layer; (2) Solution preparation: A silica microsphere suspension was prepared by sol-gel method. A certain volume of polystyrene microsphere suspension was added to the suspension in proportion to obtain a polystyrene@silica mixed suspension. (3) Preparation of micro / nano hierarchical composite structures: The suspension prepared in step (2) was uniformly dropped onto an FTO glass substrate on a spin coater. After spin coating, the polystyrene microspheres were removed at high temperature on a hot plate. ZnO seed solution was spin-coated onto a SiO2 microporous film, and then placed in a constant temperature water bath for a certain period of time. The FTO glass substrate after the ZnO nanorods were grown was annealed at high temperature in a tube furnace. (4) Thin Film Modification: Prepare a set of appropriately sized glass petri dishes, clean them thoroughly, and place one glass petri dish at the bottom of the vacuum desiccator. Add heptadecafluorodecyltrimethoxysilane to the petri dish. Place the other glass petri dish on the perforated ceramic partition in the middle of the vacuum desiccator, and place the sample to be modified into the petri dish. Simply treat the seal of the vacuum desiccator with Vaseline, and close the vacuum desiccator to ensure it is completely sealed. Connect the vacuum desiccator and the vacuum pump, adjust the glass stopcock on the vacuum desiccator, turn on the vacuum pump, and close the stopcock on the vacuum desiccator. Gently lift the entire vacuum desiccator and place it in the drying oven, allowing it to react for a certain period of time. Once the drying oven stops working and the mixture cools to room temperature, the modification is complete.
3. Step (3) as described in claim 2, characterized in that, During high-temperature calcination, the hot plate temperature is 300–400℃, the time is 20–40 min, and the speed of the homogenizer is 60–70 r / min; during zinc oxide growth, the temperature of the constant temperature water bath is 60–120℃, and the growth time is 1–6 h; during high-temperature annealing, the temperature of the tube furnace is 400–600℃, and the annealing time is 1–2 h.
4. Step (4) as described in claim 2, characterized in that, The volume of heptadecafluorodecyltrimethoxysilane added was 40–60 μL; the vacuuming time was 5–20 min; and the temperature of the drying oven was 80–100 °C.
5. A method for improving photovoltaic devices based on a self-cleaning structure of SiO2 microporous thin film coupled with ZnO nanorods. The key lies in applying this structure to improve the efficiency and performance of photovoltaic devices. The steps include: (1) FTO substrate pretreatment: First, the conductive surface of the FTO substrate is thoroughly cleaned to remove surface impurities and ensure the high quality of the subsequent deposited layer; (2) Based on the specific type of photovoltaic device (such as perovskite, sulfide, selenide, etc.), select an appropriate deposition method (such as spin coating, thermal evaporation, hydrothermal deposition, etc.) to deposit the photovoltaic absorption layer material on the self-cleaning structure of SiO2 microporous thin film coupled with ZnO nanorods; (3) A hole transport layer and an electron transport layer are deposited sequentially above the photovoltaic absorption layer. The specific materials and deposition methods are determined according to the device design. (4) The back electrode (such as gold, silver, aluminum, etc.) is prepared by thermal evaporation or magnetron sputtering, with a thickness of about 10 to 100 nm.
6. The "method for improving photovoltaic devices based on the self-cleaning structure of SiO2 microporous thin film coupled with ZnO nanorods" as described in claim 5 is an application in improving the efficiency and performance of photovoltaic devices.